2022
DOI: 10.3390/biology11071076
|View full text |Cite
|
Sign up to set email alerts
|

FAAH rs324420 Polymorphism Is Associated with Performance in Elite Rink-Hockey Players

Abstract: Genetic factors are among the major contributors to athletic performance. Although more than 150 genetic variants have been correlated with elite athlete status, genetic foundations of competition-facilitating behavior influencing elite performances are still scarce. This is the first study designed to examine the distribution of genetic determinants in the athletic performance of elite rink-hockey players. A total of 116 of the world’s top best rink-hockey players (28.2 ± 8.7 years old; more than 50% are cumu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(32 citation statements)
references
References 45 publications
(81 reference statements)
2
30
0
Order By: Relevance
“…Whether VDR rs731236 also contributes to this deficiency among the exposed individuals or, inversely, whether the SNP somehow influences tobacco consumption requires further investigation. The VDR rs731236 genotypes were also distributed differently according to the athletes’ sex, which was previously observed in a study conducted by our research group [ 22 ]. Taken together and considering the roles of these SNPs, future studies with larger cohort sizes should be conducted to reevaluate the impact of these genetic variants on TMI and MP susceptibility among high-performance athletes.…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…Whether VDR rs731236 also contributes to this deficiency among the exposed individuals or, inversely, whether the SNP somehow influences tobacco consumption requires further investigation. The VDR rs731236 genotypes were also distributed differently according to the athletes’ sex, which was previously observed in a study conducted by our research group [ 22 ]. Taken together and considering the roles of these SNPs, future studies with larger cohort sizes should be conducted to reevaluate the impact of these genetic variants on TMI and MP susceptibility among high-performance athletes.…”
Section: Discussionsupporting
confidence: 72%
“…In fact, the 385A allele (A allele; minor allele) has been associated with diminished FAAH levels and, thus, higher tolerance to pain [ 54 , 55 , 56 ]. Interestingly, the same allele was previously linked to better athletic achievements in studies conducted by our research group with rink-hockey and volleyball players [ 22 , 23 ]. In the present study, however, athletes carrying the rs324420 AA genotype were two times more prone to MP after exercise than their counterparts.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…Given the results, they noticed that experienced electronic sports competitors held higher pre-and post-competition cortisol levels compared to inexperienced participants. Silva et al (2022) revealed that the electronic game they played by generating a competitive ambiance greatly impacted the testosterone and cortisol levels of undergraduate students. In another research, Tharawadeepimuk and Wongsawat (2021) stated that contests in which a competitive ambiance is generated impact the players psycho physiologically.…”
Section: Resultsmentioning
confidence: 99%
“…Electronic sports are regarded as competitive computer games in which individuals or teams compete against each other. In addition, some researchers see it as competitive sports in which participant might expand their hand-eye coordination and mental ability when playing (Silva et al, 2022). The digital factors of electronic sports, and also the anxiety that occurs in the competitive environment of electronic sports players, lead to psychophysiological issues in the body and mind (Mehrsafar et al, 2019;La Fratta et al, 2021).…”
Section: Introductionmentioning
confidence: 99%